Ruminococcus bromii-generated acetate alleviated Clonorchis sinensis-induced liver fibrosis in mice - Li, Chun; Cheng, Changsheng; Jiang, Liping; Zhong, Xin; Huang, Guoyang; Mo, Gang; Cao, Deping; Peng, Xiaohong (Frontiers in Microbiology, 2025)
IntroductionInfection with Clonorchis sinensis (C. sinensis) has the potential to induce liver fibrosis and significantly alter the gut microbiota. However, it remains unclear how these changes in the gut microbiota, through the gut-liver axis, influence the progression of liver fibrosis. Furthermore, it is uncertain whether targeting the gut microbiota, based on the concept of the gut-liver axis, could be a potential therapeutic strategy for alleviating liver fibrosis.MethodsThe gut microbiota alterations in C. sinensis-infected mice at multiple time points were analyzed through 16S rDNA high-throughput sequencing. Ruminococcus bromii (R.bromii) therapeutic effect on C. sinensis infected mice was evaluated. Metabolic changes following produced by R. bromii were analyzed using short-chain fatty acids (SCFAs) metabolomics. Additionally, R. bromii conditioned medium (R.b CM) or its metabolites were co-cultured with two hepatic stellate cell lines (LX2 and JS1) in vitro to assess their anti-fibrotic effects. Finally, RNA sequencing was employed to investigate the specific mechanism by which acetate inhibits hepatic stellate cells (HSCs) activation.ResultsThe abundance of R. bromii increased during the inflammatory stage of C. sinensis infection and decreased significantly during the fibrosis stage. Oral gavage of R. bromii significantly inhibited C. sinensis-induced liver fibrosis while restoring the intestinal barrier. The activation of HSCs was significantly inhibited in vitro upon incubation with R.b CM. Acetate was identified as a key metabolite generated from R. bromii in R.b CM, and acetate attenuated C. sinensis-induced liver fibrosis in vitro and in vivo. Mechanistically, acetate inhibited the activation of HSCs by activating the PI3K/AKT signaling pathway to prevent the progression of liver fibrosis in mice infected with C. sinensis.DiscussionR. bromii exerted a protective effect on hepatic fibrosis by delivering acetate via the gut-liver axis to active the PI3K/AKT signaling pathway in HSCs. Furthermore, R. bromii can be used as a probiotic therapy to alleviate hepatic fibrosis.